The prevalence of anemia among children infected with Entamoeba histolytica in Baghdad - Zeki, Israa Naif; Al-Warid, Harith Saeed (Iraqi Journal of Science, 2019)
The relation between Entamoeba histolytica and anemia has lately had much attention. The aim of this study was to determine the possible correlation between anemia and parasitic intestinal infection with E.histolytica in children from Baghdad-Iraq. This study was conducted from October 2018 to April 2019 in different hospitals, primary health care centers, and primary schools. Eighty-one children participated in this study and their ages were between 1 and 12 years. The participants were divided into two groups based on their general microscopic stool examination. The first group was diagnosed as E.histolytica infected group (n=47), while no pathogens were detected in the stool samples of the second group which was considered as a healthy control (n=34). Blood samples were taken from all subjects and tested for haemoglobin level, serum ferritin, serum iron, total binding iron capacity (TBIC) and mean corpuscular volume (MCV). Nutritional status was also evaluated for all children aged â‰¥5 years old. Results showed that the prevalence of anemia was higher in children infected with E.histolytica compared with the control subjects. Anemia was largely reported among children aged 1-3 years for both E.histolytica infected children and control subjects. The results also illustrated that both haemoglobin and iron levels were significantly (pË‚0.05) lower in E.histolytica infected children compared with control subjects, while non-significant differences (pËƒ0.05) were observed in the level of ferritin between E.histolytica infected children and control subjects, although the ferritin was lower in E.hisolytica infected group. The results showed that both gender and age are significantly related to low serum iron levels in both infected and control groups. Significant relationshipswere also noticed between each of the anemia types and the nutritional status with the E.histolytca infection. Microcytic anemia as well as high records of severe malnutrition were observed in the majority of E. histolytica infected childrenThese findings indicate that anemia is more expected to be present in children infected with E.histolytica. Therefore, efforts should be focused on health education of populations at high risk of both anemia and E.histolytica.